Qualitative Research in Issues of the American Journal of Sociology during the Hegemony of the Chicago School - Piovani, Juan Ignacio (Method(e)s.)
By reviewing the articles published in the American Journal of Sociology between 1915 and 1930, this article explores the uses of terminological expressions characteristic of the qualitative approach supposedly developed by the Chicago school: case study, fieldwork, natural history, etc. First we present the intellectual and institutional aspects of the school. Then we examine a corpus of articles and reviews taking into account: the importance of the methodological reflection, the relation between the methods of the natural sciences and the social sciences, as well as the qualitative-quantitative antagonism. The main conclusion is that even if such expressions - as used in the corpus - cannot be regarded as qualitative in the current sense, particularly due to their epistemological foundations, we can observe a growing recognition of the important role of non-statistical methods in the social sciences, mainly among Chicagoans.